TRANSLANGUAGING PRACTICES IN STUDENTS' INTERNSHIP REPORTS AND THEIR IMPLICATIONS FOR THE EXISTENCE OF INDONESIAN AS A SCIENTIFIC LANGUAGE: PRAKTIK TRANSLANGUAGING DALAM PENULISAN LAPORAN MAGANG MAHASISWA DAN IMPLIKASINYA TERHADAP EKSISTENSI BAHASA INDONESIA SEBAGAI BAHASA ILMIAH - Rosalina, Erlyn (Jurnal Kata, 2025)
This study examines translanguaging practices in students’ internship reports and their implications for the sustainability of Bahasa Indonesia as an academic language. The increasing use of English terminology in professional academic writing reflects the integration of global language resources. This study aims to identify forms of translanguaging, analyze their distribution and functions, and explain their impact on the status of Bahasa Indonesia. A qualitative descriptive approach was employed using thematic analysis of 85 lexical data categorized into borrowing, hybrid, and mixing forms. The findings indicate that translanguaging is dominated by borrowing, with full English structures as the primary pattern, while Bahasa Indonesia remains the main syntactic framework through mixed constructions. These results suggest that translanguaging enhances terminological precision and communication efficiency but also reflects the growing dominance of global language. Therefore, translanguaging represents an adaptive practice that negotiates between professional communication needs and the sustainability of Bahasa Indonesia in academic contexts.